Coplanar binuclear group 4 post-metallocene complexes supported by chelating μ-(σ-aryl) ligands: characterisation and olefin polymerisation catalysis - Li, Yufang; Liu, Qian; Bao, Junhui; Yiu, Shek-Man; Chan, Michael C. W (Dalton transactions : an international journal of inorganic chemistry, 2023)
The report concerns expansion of the previously developed M-[O,N,C] [pyridine-2-phenolate-6-(σ-aryl)] catalyst system into rigid, coplanar bimetallic assemblies, which afford metal-metal distances that are predetermined yet amenable for cooperativity, as well as locked-in " syn " orientation of binding sites that offer the same direction of access for substrates. The binuclear complexes are generated in a regioselective manner to yield para hydrogen atoms (not ortho ) at the central μ-aryl moiety, and have been characterised by multinuclear NMR spectroscopy. The " anti " (showing opposite directions of access) and mononuclear analogues have also been prepared for comparison purposes. Six syn -type bimetallic derivatives of Ti, Zr and Hf have been characterised by X-ray crystallography, to reveal metal-metal separations of 6.3-6.7 Å. For ethylene and ethylene/1-octene polymerisation reactions in conjunction with trityl borate, the syn -Ti 2 catalysts display superior efficiencies and produced polymers with higher M w values than for the anti and mono-Ti congeners, thus indicating the possibility of favourable enchainment interactions and cooperative reactivity. Rigid binuclear assemblies with M M distances and syn binding sites that are amenable for cooperative reactivity have been structurally characterised; the Ti 2 catalysts are more active than anti and mono-Ti controls and produced higher- M w polymers.